Analysis of Five-Year Malaria Prevalence at the Federal Teaching Hospital, Ido-Ekiti, Nigeria - Mmaduakor, Chika; Ngwu, Benitho; Ojo-Lawal, Sherifat; Oluwafemi, Glory; Peter, Olumuyiwa James; Raso, Mario (Jambura Journal of Biomathematics (JJBM), 2025)
Malaria remains a major public health problem globally, with Nigeria accounting for approximately 27% of the global burden. Chronological analysis of malaria data is vital for evaluating the performance of malaria prevention programmes in Nigeria. Therefore, the objective of this study is to determine the malaria prevalence rate at the Federal Teaching Hospital, Ido-Ekiti (FETHI), over a five-year period. Data from 484 suspected malaria patients who visited the hospital between 2019 and 2023 were collected and analysed. Logistic regression was used to evaluate the relationship between positive blood film results and potential associated factors. Among all presumptive cases, 307 (63.4%) were female. The annual malaria prevalence ranged from 30.4% to 54.2%, with an overall prevalence of 42.32% (95% CI: 34.3%–54.4%). Two Plasmodium species were detected: Plasmodium falciparum (98 cases, 47.3%) and Plasmodium vivax (83 cases, 40.1%). A higher proportion of cases were recorded in December, January, and May (50%, 51.2%, and 51.4%, respectively). Patients who visited the hospital in January were twice as likely to be infected compared to those in April [OR: 2.29; 95% CI: 0.88–6.18; p = 0.037]. Males were half as likely to be infected as females [OR: 0.47; 95% CI: 0.30–0.72; p = 0.00066]. Malaria remains a significant concern in the studied location. Therefore, malaria control programmes need to be strengthened to reduce its impact.